2017
DOI: 10.3389/fnagi.2017.00203
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline in the Variation of Dynamic Functional Connectivity: A Resting State Analysis

Abstract: Normal aging is typically characterized by abnormal resting-state functional connectivity (FC), including decreasing connectivity within networks and increasing connectivity between networks, under the assumption that the FC over the scan time was stationary. In fact, the resting-state FC has been shown in recent years to vary over time even within minutes, thus showing the great potential of intrinsic interactions and organization of the brain. In this article, we assumed that the dynamic FC consisted of an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 72 publications
5
48
0
Order By: Relevance
“…We found that this typical speed decreases with age, and this not only for empirical rest and task data but also for both considered surrogate types. Overall, our findings hint toward a reduced network variability in aging, in the same direction as other dFC analyses (Chen et al, 2017) and previous reports of reduced variability in elderly already at the level of the BOLD signal itself (Grady & Garrett 2014). Other studies, however, reported increased "noise" in the elderly relative to the younger subjects, at least at specific scales and in certain regions (Yang et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that this typical speed decreases with age, and this not only for empirical rest and task data but also for both considered surrogate types. Overall, our findings hint toward a reduced network variability in aging, in the same direction as other dFC analyses (Chen et al, 2017) and previous reports of reduced variability in elderly already at the level of the BOLD signal itself (Grady & Garrett 2014). Other studies, however, reported increased "noise" in the elderly relative to the younger subjects, at least at specific scales and in certain regions (Yang et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…As we age, our brain undergoes characteristic structural and functional changes, with a tendency toward increased structural 'disconnection' (Salat, 2011), disruptions in rs-FC (Andrews-Hanna et al, 2007;Betzel et al, 2014) and modified structural-to-functional connectivity inter-relations (Zimmermann et al, 2016). Analogously, changes in dFC have been reported at the level of the temporal stability of FC network modules (Davison et al, 2016;Schlesinger et al, 2016), general or specific network variability (Qin et al, 2015;Chen et al, 2017), "FC state" occupancy (Hutchison & Morton, 2015;Viviano et al, 2017), and complexity of phase synchrony (Nobukawa et al, 2019). We complement these previous findings and show that dFC random walks may occur at an increasingly reduced speed and complexity with age, slowing down and becoming increasingly more "random".…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…9 Whereas previous studies have primarily reported results from various estimates of static FC (sFC; the temporal correlation between two brain regions across the entire time-series), there is an increasing awareness of the relevance of dynamic FC (dFC; the variability in the temporal correlations across the time-series). 12,13 Interestingly, sFC and dFC capture distinct properties of brain network dynamics, 14,15 and may therefore provide complementary information in depression. 16 Here, in order to address symptom heterogeneity in depression, we used high dimensional data-driven clustering (HDDC) 17 based on item scores on the Beck's Depression (BDI-II) and Beck's Anxiety (BAI) inventories to identify groups of individuals with distinct symptom profiles among 1084 subjects with or without a history of a diagnosis of depression.…”
Section: Introductionmentioning
confidence: 99%